2018
DOI: 10.4103/abr.abr_35_18
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Dietary Patterns with Blood Pressure in Iranian Army Staffs

Abstract: Background:Hypertension is one of the most common noncommunicable diseases in the world. One of the most effective factors on blood pressure (BP) is nutrition. The aim of this study was to examine the relationship between dietary patterns and BP among military staffs.Materials and Methods:The study was carried out among 405 military staffs between 22 and 51 years old. Demographic, anthropometric information, and BP of participants were evaluated by standard methods. The dietary intakes were collected using a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…It is shown that with aging [ 54 ] and increasing BMI [ 55 ], SBP rises. According to the study of Moghaddam et al [ 56 ], the association between dietary patterns and SBP became non-significant after adjusting for age, sex, marital, smoking, income, body mass index, waist-to-hip ratio, family history of hypertension, energy intake and physical activity level. Another interesting finding of this study was that consuming moderate FODMAP foods was associated with lower SBP, a significant in the second tertile.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that with aging [ 54 ] and increasing BMI [ 55 ], SBP rises. According to the study of Moghaddam et al [ 56 ], the association between dietary patterns and SBP became non-significant after adjusting for age, sex, marital, smoking, income, body mass index, waist-to-hip ratio, family history of hypertension, energy intake and physical activity level. Another interesting finding of this study was that consuming moderate FODMAP foods was associated with lower SBP, a significant in the second tertile.…”
Section: Discussionmentioning
confidence: 99%